Membangun Desain API Internet of Things pada Usaha Tani Kentang - Nainggolan, Mai Fernando (JURNAL AGRIUST, 2025)
The Internet of Things is a technology that allows objects to connect to other objects or users via the Internet. In the agricultural sector, the Internet of Things allows farmers to monitor the nutritional conditions of their plants and field conditions. The purpose of this research is to make it easier for farmers to fertilize and water plants, record plant development, and check nutritional conditions in agricultural businesses and physiological conditions in the field in real-time. Farmers obtain soil and field physiological information from soil sensors and field sensors that have been installed in the soil. The data is sent by the sensor to a MySQL database via an API accessed by the ESP32 microcontroller and can be displayed on a mobile application. From several experiments conducted, the results show that all data accessed by the microcontroller produces 100% in JSON format.